Advanced Elastomers (IntechOpen, 2023)
This book provides an extensive overview of current trends in the area of elastomers and their composites from the chapters contributed by internationally recognized specialists. The book deals with novel synthesis, modelling and experimental methods in elastomers. Contents include: new approach to crosslinking, liquid crystal elastomers, nanocomposites, smart elastomers, elastomers in microelectronics and microfluidics, elastomers in cement concrete and mortar, experimental testing and modelling. Each section demonstrates how enhancements in materials, processes and characterization techniques can improve performance in the field of engineering. The book provides a unique opportunity to discover the latest research on elastomer advances from laboratories around the world. This book addresses to industrial and academic researchers in the fields of physical, chemical, biological sciences and engineering.